حجاجية الأفعال الكلامية في نماذج مختارة من خطاب التنمية البشرية لإبراهيم الفقي - لعيد, حند; مهدي عزالدين, شنين (جامعة الوادي - University of Eloued, 2021)
يعد الحجاج فنا من فنون الإقناع؛ حيث أن مبدأه يعتمد أساسا على تقديم الأدلة والبراهين المخاطب بغية الإقناع والتأثير في السامع. لقد ظهر مصطلح الحجاج منذ القديم إذ أنه قد ظهر في عصر أفلاطون وأرسطو، وقد لقي اهتماما كبيرا في عصرنا هذا حيث اهتم به الغربيون بمختلف مدارسهم وتوجهاتهم الفكرية ذلك أن الحجاج عنصر مهم في حياة الناس؛ ولم يكن العرب بمنأى عنه هذا الاهتمام فقد كان لهم باع كبير في هذا معالجة هذا الفن اصطلاحا وإجراء . وتجدر الإشارة إلى أن الحجاج مجال من مجالات التداولية يرتكز في سبيل توصيل الفكرة للمخاطب وجعله ينصاغ لمراد المتكلم المرسل النموذجي للكتل الكلامية ذات الحمولة الدلالية التداولية وعلى مرتكزات عدة أيضا منها الحالية ومنها المقالية. وفي المقالية ارتأينا الوقوف على واحدة منها ألا وهي الأفعال الكلامية. وفي سبيل الوقوف على تجليات هاته الآلية بعدها مفتاحا هاما في فهم التواصل البشري المعتمد إجبارا على عنصر الحجاج فإننا قد اخترنا لها مجالا مشهورا يعرفه العام والخاص ألا وهو خطاب التنمية البشرية ممثلا في الأستاذ إبراهيم الفقي من خلال محاضراته المسموعة والمرأية وسنحاول إبراز مدى تأثير وسائل الإقناع ممثلة في الأفعال الكلامية بأبعادها التداولية الحجاجية ,من خلال العينات النموذجية الفعلية الممثلة في جمهور إبراهيم الفقي، وهذا ما سيتناول بالدراسة والتحليل في هذا المقال. Abstract: The persuasion is an art of persuasion. As its founder relies on providing opinion and evidence. The term persuasion appeared since ancient times as it appeared in the era of Plato and Aristotle, and it has received great attention in our time, as Westerners have paid attention to it in their various schools and intellectual orientations, so that pilgrims are an important element in people's lives The Arabs were not immune to this interest, as they had a great deal of knowledge in this art dealt with convention and procedure. It should be noted that the pilgrims are based in order to communicate the idea of the addressee and make him obey to the meaning of the typical sender of the speaking blocks of semantic load on the foundations of several of the current ones, including the article, and in the killing, we decided to stand on one of them, namely verbal actions. In order to find out the manifestations of this mechanism, after which it is an important key in understanding human communication adopted forcing the pilgrims, we have chosen for it a well-known field known to the public and the private, which is the discourse of human development represented by Mr. Ibrahim Al-Feki through his audio and video lectures, and we will try to clarify the extent of the influence of persuasion methods represented On verbal verbs in viewers or actual model samples represented in the audience of Ibrahim al-Feki, and this is what is covered in the study and analysis in this article.
مقال
Keywords: الحجاج؛ آليات الحجاج اللغوي؛ الأفعال الكلامية؛ الخطاب؛ التداولية؛ التنمية البشرية إبراهيم الفقي.